Proliferative myositis: case report and review of the literature - Abdellatif Bensalah (Radiology Case Reports, 2021)
Proliferative myositis is a rre benign pseudosarcomatous inflammatory process that rapidly grows in muscles. Its clinical and radiological features may, however, simulate a malignant tumor. We report ultrasound and MRI appearances of a 63 years-old woman with no significant anterior pathological history presented to our radiology department with two weeks history of a painful mass in the left musculus latissimus dorsi, increasing progressively in size, without history of recent trauma. This study describes the imaging features of these pseudo inflammatory process, which may help to suggest the diagnosis, but the imaging finding are variable and nonspecific. However, histopathological examination is usually recommended to confirm the diagnosis. In our case, the final diagnosis was proved by ultrasound-guided biopsy. We also review the imaging features of this entity in the current literature.